T Lymphocyte Autoreactivity in Inflammatory Mechanisms Regulating Atherosclerosis - Elisabetta Profumo; Brigitta Buttari; Luciano Saso; Raffaele Capoano; Bruno Salvati; Rachele Riganò (The Scientific World Journal)
Atherosclerosis has been clearly demonstrated to be a chronic inflammatory disease of the arterial wall. Both cells of the innate and the acquired immune system, particularly monocytes and T lymphocytes, are implicated in the atherogenic process, producing different cytokines with pro- and anti-inflammatory effects. The majority of pathogenic T cells involved in atherosclerosis are of the Th1 profile, that has been correlated positively with coronary artery disease. Many studies conducted to evaluate the molecular factors responsible for the activation of T cells have demonstrated that the main antigenic targets in atherosclerosis are modified endogenous structures. These self-molecules activate autoimmune reactions mainly characterized by the production of Th1 cytokines, thus sustaining the inflammatory mechanisms involved in endothelial dysfunction and plaque development. In this paper we will summarize the different T-cell subsets involved in atherosclerosis and the best characterized autoantigens involved in cardiovascular inflammation.